Japan's valsartan clinical trials shambles; time for fundamental changes. (16th February 2023) - Ozaki, Akihiko; Harada, Kayo; Murayama, Anju; Saito, Hiroaki; Sawano, Toyoaki; Tanimoto, Tetsuya; Shrestha, Sunil; Bhandari, Divya; Crump, Andy
Abstract: Japan's Diovan ® /valsartan 'scandal' has received sensational coverage in the nation's media since 2012. Publication of fraudulent research and their subsequent retraction boosted and then curtailed the use of what was a useful therapeutic drug. Some authors of the papers resigned, others disputed the retractions and resorted to legal counsel to protect themselves. One individual, an undeclared Novartis employee involved in the research, was arrested. A complex and virtually unwinnable case was brought against him and Novartis, claiming that data alteration amounted to false advertising, but lengthy criminal court cases resulted in the case failing. Unfortunately, key elements, including conflicts of interest, pharmaceutical company interference in trials of its product, and the role of the institutions involved, have been effectively ignored. The incident also emphasised the fact that Japan's unique society and approach to science does not conform well to international standards. Although the supposed impropriety caused the appearance of a new Clinical Trials Act in 2018, the law has been criticized for being ineffectual and simply increasing clinical trial bureaucracy. This article examines the 'scandal' and identifies where changes must be made to clinical research and the roles of the various stakeholders in Japan to increase public trust in clinical trials and biomedical publications. Highlights: Valsartan 'scandal' identified major failings in Japanese healthcare and research. Purportedly fraudulent research papers resulted in their subsequent retraction. A criminal case against Novartis and its employee resulted in not guilty verdicts. Despite new laws being enacted, nothing has changed and serious issues remain unresolved.